Pendampingan Masyarakat Melalui Pengajian Tematik untuk Meningkatkan Toleransi Antar Umat Islam di RW 03 Kampung Tanjungsiang - Rosenda, Diden; Saepudin, Aep; Asmaini, Nur (Yayasan Sagita Akademia Maju, 2024)
This community assistance aims to increase tolerance between Muslims in RW 03 Kampung Tanjung, Tanjungsiang Village, which has around 1,200 residents who have various beliefs in schools of thought, thus hindering togetherness and tolerance. The aim of assistance is to establish Islamic Brotherhood and tolerance, minimizing divisions. The mentoring method uses interactive teaching methods through thematic recitations in the form of tabligh akbar with the title